Evaluation of antibacterial activity of two natural bio-preservatives formulations on freshness and sensory quality of ready to eat (RTE) foods. (March 2018) - Harich, Mehdi; Maherani, Behnoush; Salmieri, Stephane; Lacroix, Monique
Abstract: The antibacterial activity of two natural antibacterial formulations based on lemongrass essential oil/citrus extract/lactic acid for F2 (with ratio of 0.01:0.1:1) and oregano/citrus extract/lactic acid for F6 (with ratio of 0.01:0.1:1) was studied against several pathogens ( Listeria monocytogenes, Escherichia coli and Salmonella Typhimurium) and non-pathogenic bacteria ( Listeria Innocua, Escherichia coli ATCC 25922, and Salmonella enterica ). The in vitro inhibition capacity (IC %) of F2 and F6 formulations demonstrated their high antimicrobial potential against pathogenic and non-pathogenic bacteria. In addition, in vitro minimum inhibitory concentration (MIC) of F2 and F6 formulations exhibited a lower MIC (higher antibacterial properties) against pathogenic and non-pathogenic bacteria compared to sodium benzoate. Furthermore, in situ antimicrobial capacity of two natural formulations (F2 and F6) was assessed on ready to eat vegetables and fruits (pre-cut red peppers, cranberries and pre-cut/pre-fried potatoes) against targeted bacteria; it's important to mention that peppers and cranberries were frozen and then thawed before treatment and storage, however pre-fried potatoes were fresh. The in situ results showed that both coatings allowed a significant reduction (P ≤ 0.05) of pathogenic bacteria in cranberries (e.g. in presence of F2 formulation: 1.5, 2.3, 1.7 log reduction of L. monocytogenes, E. coli and S . Typhimurium populations, respectively) and in red peppers (1.3, 0.85 and 2 log reduction of L. monocytogenes, E. coli and S . Typhimurium in presence of F6). Results obtained on pre-fried sliced potatoes packed under modified atmosphere (MA), showed that F2 allowed a 0.5 and 1.5 log reduction of E. coli and S. Typhimurium respectively at day 10. On the other hand, F6 allowed a 0.5 and 1.1 log reduction of E. coli and S. Typhimurium respectively at day 10. The sensory analysis of red peppers and potatoes treated with F2 and F6 formulations suggested that both formulations were acceptable in terms of organoleptic attributes. Therefore, their sensorial attributes could be accepted for further commercialization. Highlights: In vitro results showed that natural bio preservatives were more effective than sodium benzoate. In situ results showed they reduce foodborne pathogens and non-pathogens in RTE Foods. The sensory analysis confirmed formulations are acceptable in terms of organoleptic attributes. Findings approved that sodium benzoate can be replaced by natural antibacterial formulations.